Social Work Student Perceptions of Labor Trafficking - Mulhern, Margaret (2014)
Human Trafficking in Florida is a growing issue that affects individuals and communities on a micro, mezzo, and macro level. Although legislative efforts and changes in agency policies have raised awareness about this problem, limited awareness and research examines awareness of labor trafficking as one form of human trafficking. This exploratory-descriptive study used a convenience sampling technique to explore the perceptions of 45 Bachelors (BSW) and Masters (MSW) level social work students on the prevalence and nature of labor trafficking. The findings from the research show students have a general idea of labor trafficking and believe in equal access to human rights for victims. However, majority of students were unaware of current legislation to aid victims in Florida, and the prevalence of men as victims. Implications from this study show a need for further education within social work policies that aid labor trafficking victims, and a need for additional research to identify specific ways students can learn about human trafficking